Implementasi Pembelaan Terpaksa (Noodweer) sebagai Alasan Penghapus Pidana dalam Kasus Penganiayaan - Clayment Claudio Jap; R. Rahaditya (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Acts of abuse can be carried out by people in a state of coercion to protect themselves from the threat they face. This is known as Noodweer (forced defense), which will be a consideration for the judge in forming a legal decision. This research is aimed at analyzing the implementation of forced defense as a reason for abolition of punishment in cases of abuse, by using a case study at Donggala District Court Number 32/Pid.B/2021/PN Dgl. The research approach implemented is a qualitative approach, with a doctrinal or normative legal research design. In carrying out this research, the author used a case research approach, which was carried out by analyzing in depth cases that have direct relevance to the legal issue being studied. The research findings indicate that the defendant named Khofifa was declared free from punishment, because there were two main elements that could be considered by the court, namely the physical threat received by Khofifa and the threat to his honor caused by the actions of Maghfira, who was a witness. Not only that, this action must also be seen in the context of the physical condition of Khofifa who is pregnant, which of course requires extra protection for her safety. In deciding Khofifa's case, the judge evaluated several key things related to Article 49, namely the existence of attacks or forms of unlawful threats, threats to honor and personal safety, the proportionality of actions, and referred to the condition that there was no other recourse available.